Keterkaitan Akses Sanitasi dan Tingkat Kemiskinan: Studi Kasus di Propinsi Jawa Tengah - Bhimo Rizki; Samsubar Saleh (Universitas Islam Indonesia, 2007)
The Millennium Development Goals (MDGs) describes that there exist the inter¬dependent relationship between sanitation and poverty rate. In fact, developing and improv¬ing in sanitation aspect will reduce indirectly poverty. The goal of this study is to investigate the relationship between sanitation and poverty in the case of all regencies/municipalities in the central Java Provinces.The results find that the factors affecting sanitation are the gross regional domestic product (GRDP) per capita, income distribution, and the cultural awareness of household on health related to sanitation. In other hand, sanitation accessibility of household could affect economic and social aspect such as poverty rate and the gross regional domestic product per capita. This study also shows that Banyumas, Purbalingga, Banjarnegara, Purworejo, Wonosobo, Rembang, Demak, Pekalongan, Pemalang, and Tegal are some regen¬cies/municipalites in Central Java province which their sanitation access is less condusive.Keywords: Human Development Indexes, Sanitation, Millennium Development Goals, Poverty, GRDP per capita